Anne Donadey. The Algerian War in Film Fifty Years Later, 2004-2012. Lexington Books, 2020. - Anna Rocca (Studies in 20th & 21st Century Literature, 2023)
Review of Anne Donadey. The Algerian War in Film Fifty Years Later, 2004-2012. Lexington Books, 2020. 246 pp.
Keywords: Films; Algerian War; Anamnesis; Colonialism; Post-Colonialism; Algeria; France